Studi Komparasi Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) dengan Kooperatif Tipe Jigsaw terhadap Aktivitas dan Hasil Belajar TIK (Studi Kasus di Kelas VIII SMP Negeri 5 Singaraja Tahun Ajaran 2012/2013) - Ida Purnamasari, Putu; Gede Sunarya, I Made; Windu Antara Kesiman, Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
The purpose of this study to determine (1) the influence of differences in the use of cooperative learning model type Group Investigation (GI) with the Jigsaw cooperative learning activities toward Information Computer Technologi (2) the difference of influence in the use of cooperative learning model type Group Investigation (GI) with the type of cooperative Jigsaw toward Information Computer Technologi learning outcomes. It was a type of quasiexperimental study research design Posttest-Only Control Group Design. The study population was all eighth grade students of SMP Negeri 5 Singaraja school year 2012/2013. As the sample in this study is a class VIII D and VIII E which was 60. Class VIII D is used as a first-class experiment with cooperative learning model type Group Investigation (GI) and Class VIII E as a second experiment with the Jigsaw cooperative model type. Based on the analysis of the data obtained, the test of normality and homogeneity of learning activities both normal distribution and homogeneous groups. Hypothesis test results of students' learning activities stated that there were significant differences influenced the use of cooperative learning model type Group Investigation with the Jigsaw cooperative learning activities toward Information Computer Technologi. Analysis of student learning outcomes data obtained, tests of normality and homogeneity distributed normal and homogeneous. The Results of hypothesis testing learning outcomes stated that there were significant differences influence the use of cooperative learning model with the Group Investigation Jigsaw cooperative ICT on learning outcomes. This activities shows that the result of cooperative learning by using learning media cooperative type of group investigation (GI) is different and better than jigsaw media cooperative learning.